Some Trials to Afforest Red Marl Soil - Singh, Jagjit (Indian Forester, 1961)
In order to reclaim lands with red marl soil, which had reached an advanced stage of erosion owing to biotic, edaphic and climatic factors, a large number of species considered suitable were tried since 1937 in the Suli Tila Experimental Plot at Nurpur, Kangra, to study their efficacy. In the beginning reliance was placed on succulents, but later on various other soil binding plants were also introduced. The results of the trials are summarised in this note: